CONOCIMIENTO SOBRE ANEMIA FERROPÉNICA EN MADRES DE NIÑOS DE 06 A 36 MESES ATENDIDOS EN EL PROGRAMA SIN ANEMIA DEL HOSPITAL NAYLAMP, CHICLAYO – 2021 - Alarcón Vallejos, Lucy Marleny (2022)
Objective: To determine the level of assess knowledge of iron deficiency anemia in mothers of children from 06 to 36 months of Naylamp Hospital, Chiclayo – 2021. Methodology: This research belongs to the quantitative approach; it is a nonexperimental type with a simple descriptive design cross-sectional Study. The data collection technique used was the survey; and its instrument the questionnaire to assess knowledge of iron deficiency anemia in mothers of children from 06 to 36 months. Participants: The sample consisted of 160 mothers of children from 06 to 36 months attended in the Program without Anemia of the Naylamp Hospital, Chiclayo 2021 Results: Regarding the variable knowledge about iron deficiency anemia of a total of 100%, 91% of mothers of children from 06 to 36 months do know, while 9% do not know. According to the dimensions, the degree of knowledge about the definition (98%), the diagnosis (97.5%), the treatment (91%), the Signs and Symptoms (97%), the Causes (94%), the consequences (92%), Prevention (91%) and Importance for an adequate diet (83%). Conclusions: It has been possible to describe those mothers do know about iron deficiency anemia, where the results show that 9% of mothers do not know about iron deficiency anemia and 91% of mothers know about iron deficiency anemia. Keywords: Knowledge, Iron deficiency anemia y Mothers